COLLAGEN AS THE BASIS OF BONE TISSUE AND ITS DEGRADATION IN INFLAMMATION (International Educators Conference, 2025)
Type I collagen forms the basis of the organic matrix of bone tissue and plays a key role in ensuring its strength, elasticity, and resistance to mechanical stress. In inflammatory processes, such as acute hematogenous osteomyelitis, the degradation of collagen fibers is activated, which disrupts the structural integrity of bone tissue. This article explores the structure and functions of type I collagen in bone tissue, as well as the mechanisms of its degradation during inflammation and the diagnostic significance of its degradation products.